Land Snail Fauna of Sabah, Borneo, Malaysia - Rina Uchida; Bakhtiar Effendi Yahya; Abdul Hamid Ahmad; Arney Sapaat; Kiyonori Tomiyama (Malacological Society of Japan, 2013)
We surveyed the land snail fauna of 13 localities including three limestone outcropsin Sabah, Borneo, Malaysia. Land snails were sampled using manual collection and identified tospecies level where possible. In this study, a total of 39 species was recorded. Species diversityin limestone areas was higher than that in non-calcareous areas. The genus Opisthostoma wasfound in all the 3 limestone outcrops. A random sample of about 20 shells of this genus fromeach site contained single but unique taxa among the three limestone outcrops. The threelimebtone outcrops were isolated by more than 20 km from one another. This result confirmedthe high endemicity of this genus. At areas deforested and perturbed by humans, we found twoinvasive species, Bradybaena similaris (Rang, 1831) and Subulina octona (Bruguibre, 1792),which have been widely spread over the world.